Analysis of the Negative Impact of Gadget Use on Elementary School Students: A Systematic Literature Review - Cindy Aulia Sari; Junaidi; Maya Setia Priyadi; Elizar (Journal for Lesson and Learning Studies, 2026)
The use of gadgets among elementary school students has increased alongside the rapid development of digital technology; however, this growth has not been adequately balanced with proper supervision and understanding of its impact on children’s development. This condition has the potential to cause various problems, including behavioral changes, decreased social interaction, reduced learning concentration, as well as emotional and health-related issues. This study aims to analyze and synthesize findings from previous studies regarding the impact of gadget use on elementary school students through a Systematic Literature Review (SLR) approach. The subjects of this study consisted of ten relevant scientific articles focusing on elementary school students. Data were collected through literature searches across various scientific databases using predetermined inclusion and exclusion criteria, with an article synthesis matrix employed as the research instrument. The data were analyzed using a descriptive-qualitative approach to identify patterns, trends, and relationships among the findings of previous studies. The results indicate that uncontrolled gadget use tends to have negative effects on children’s academic, social, emotional, and health aspects. However, properly directed gadget use also has the potential to support the learning process. This study concludes that controlling gadget use, providing parental and teacher supervision, and strengthening digital literacy are essential factors in minimizing the negative impacts of gadget use among elementary school students. The implications of this study highlight the importance of educational and collaborative strategies involving families, schools, and the social environment in promoting healthy and balanced gadget use among children.